THE PROBLEM OF MAXIMUM IMPRISONMENT TERMS FOR JUVENILES UNDER THE JUVENILE CRIMINAL JUSTICE SYSTEM ACT: A CASE ANALYSIS OF CONCURRENCE OF OFFENSES - Bodro Aji Negoro; Setiawan Noerdajasakti; Abdul Madjid (CV. RADJA PUBLIKA, 2025)
The maximum imprisonment term of ten years for juveniles under Law Number 11 of 2012 on the Juvenile Criminal Justice System (UU SPPA) presents a serious dilemma when applied to cases with aggravating circumstances, such as recidivism or concurrence of offenses. Judicial practice has shown deviations from this provision, one of which is reflected in the Penajam District Court Decision Number X/Pid.Sus-Anak/2024/PN Pnj, which sentenced a juvenile offender to twenty years of imprisonment for premeditated murder and aggravated theft, where trial findings also revealed postmortem sexual assault on the victim’s body. This decision sparked normative debates on whether the judge had exceeded the statutory maximum penalty for juveniles as stipulated by law, or instead fulfilled the demand for substantive justice. The complexity of this issue becomes more pronounced in the context of globalization, where today’s juveniles experience accelerated cognitive and emotional maturity due to extensive exposure to technology and global interaction—conditions that differ significantly from those in 1989, when the Convention on the Rights of the Child set the maximum age limit for juveniles at eighteen years. Employing a normative-juridical method through statutory and case study approaches, this research analyzes the normative conflict between the UU SPPA and judicial practice, and identifies a legal vacuum that requires legislative reconstruction, particularly in formulating clearer sentencing guidelines for juveniles in cases involving aggravating circumstances.